Don't follow me, I'm lost a memoir of Hampshire College in the twilight of the 80's - Rushfield, Richard (Gotham Books, 2009)
Documents the author's experiences at a progressive Massachusetts college, shedding his conservative California upbringing in favor of a hippie culture shaped by Grateful Dead music, insomniac filmmaking, and political correctness.